Titanium vacancy-rich Ti3C2-based cobalt monatomic two-dimensional material as well as preparation method and application thereof
By anchoring Co single atoms on the Ti3C2 substrate and preparing Co/SA-Ti3C2 material, the agglomeration and activity stability problems in single atom catalysts are solved, and the effect of efficient removal of OMPs in water is achieved, reducing energy consumption and cost.
Patent Information
- Application Number
- CN202411424677.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-10-12
AI Technical Summary
The problems of metal atom agglomeration, poor selection of 1O2 in existing single-atom catalysts and difficult to compatible with catalytic activity and structural stability in existing single-atom catalysts lead to low efficiency and high cost in OMPs removal in water treatment.
Co/SA-Ti3C2 material is prepared by anchoring Co single atoms on a Ti3C2 substrate, and the coupling method of etching-peel-reduction is adopted to maintain the two-dimensional layered structure of the material, and the dispersion and catalytic activity of cobalt single atoms are improved. Reduce energy consumption.
It realizes efficient activation of PMS at room temperature, rapidly degradation of OMPs in water, reduces operating costs, improves catalytic activity and structural stability, and avoids metal ion dissolution and water pollution.
Smart Images

Figure CN119158604A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of water pollution control of environmental functional materials, and in particular to a Ti3C2-based cobalt single-atom two-dimensional material rich in titanium vacancies, and a preparation method and application thereof. Background Art
[0002] The presence of organic micropollutants (OMPs) in the water environment is an important environmental issue facing the world today. OMPs are a class of chemicals that include personal care products, endocrine disruptors, and antibiotics. They are generally characterized by low concentration, difficulty in degradation, persistence, and bioaccumulation. OMPs are widely available and cannot be completely removed in traditional water treatment processes, which may have potential negative impacts on ecosystems and human health. Oxidation pathways are often used in wastewater treatment processes, and peroxymonosulfate-based advanced oxidation processes (PMS-AOPs) have been widely studied in the field of water pollution control. PMS-AOPs can produce highly active free radicals (SO4 ·- and ·OH) and highly selective non-radicals ( 1 O2, high-valent metals and metal-PMS complexes), thereby achieving the mineralization and oxidation process of OMPs. However, in actual water bodies, when inorganic anions (such as Cl - 、SO4 2- 、NO3 - When PMS coexists with target pollutants, it will consume highly active free radicals and inhibit the degradation of pollutants, while reducing the utilization efficiency of PMS and may produce more toxic byproducts. 1 O2-mediated non-radical PMS-AOPs have the advantages of long half-life, strong selectivity and strong anti-interference ability, and are considered to be a promising candidate to replace free radicals (SO4 ·- and ·OH) as the dominant oxidation process. However, in traditional catalytic materials, the activation PMS process generates 1 O2 has low selectivity and is accompanied by problems such as metal ion dissolution and increased water chromaticity. Therefore, in the field of water pollution control, it is urgent to develop new catalysts to increase the dominant active substances in the process of activating PMS. 1 Selective generation of O2 and ensuring no new environmental issues are introduced while treating wastewater containing OMPs.
[0003] In single atom catalysts (SACs), metal atoms are completely dispersed on the support at the atomic level, thus achieving maximum exposure of active sites and forming a unique electronic structure, which is beneficial for activating PMS generation. 1 O2 shows great potential. Usually SACs are based on carbon or heteroatom-doped carbon and are prepared by pyrolysis. After undergoing a high-temperature process, the loaded metal atoms tend to agglomerate, which in turn affects the catalytic activity of SACs. In addition, high-temperature treatment often requires a lot of energy, which can easily lead to high material synthesis costs and is not conducive to environmental safety. Summary of the invention
[0004] The purpose of the present invention is to provide a Ti3C2-based cobalt single-atom two-dimensional material rich in titanium vacancies, a preparation method and application thereof, so as to solve the problems of atomic agglomeration, 1 The problems include poor O2 selectivity and the difficulty in compatibility between catalytic activity and structural stability.
[0005] In view of the problems that the current domestic traditional water treatment technology is insufficient in removing OMPs, the catalytic material has low activity and poor stability in actual water bodies, the present invention has independently developed a preparation method to successfully anchor single-atom Co on a Ti3C2 substrate (such as Figure 2 c), and Co / SA-Ti3C2 material (SA stands for single atom) was prepared. This preparation method not only reduces the problem of atomic agglomeration in SACs, but also balances the co-enhancement barrier between catalytic activity and structural stability. Compared with traditional single-atom catalytic materials, Co / SA-Ti3C2 prepared by this method is more effective in treating difficult-to-degrade organic micropollutants in water, and its manufacturing and operating costs are lower.
[0006] A method for preparing a two-dimensional Ti3C2-based cobalt single-atom catalytic material rich in titanium vacancies is as follows:
[0007] (1) Add 4 g of LiF into a polytetrafluoroethylene beaker containing 60 mL of concentrated hydrochloric acid solution, stir mechanically at 650 rpm, and after complete dissolution, slowly add 2 g of MAX powder and stir in a water bath for 24 h;
[0008] (2) After removing the white floating layer of the mixed solution, the solution is centrifuged and washed until the pH of the supernatant is close to neutral, and the solid precipitate is collected;
[0009] (3) Transfer the solid precipitate to a screw-capped reagent bottle, continue shaking until a dark green viscous substance can be seen hanging on the inner wall of the reagent bottle, fill it with nitrogen and store it at low temperature;
[0010] (4) The dark green viscous substance in step (3) was dispersed in distilled water to prepare an aqueous solution with a concentration of 1 mg / mL, 10 mL of NaBH4 aqueous solution was added, and the mixture was mixed and stirred at 650 rpm for 30 min, and then ultrasonically treated in an ice bath for 1 h. The treated solution was then centrifuged and freeze-dried to collect the solid powder;
[0011] (5) The solid powder in step (4) was dispersed in distilled water to prepare 500 mL of aqueous solution, and 22.88 mL of Co(NO3)2·6H2O solution was slowly added under stirring conditions, magnetic stirring was performed for 30 min, ultrasonic treatment was continued for 1 h, and then centrifugal washing and freeze-drying were performed for 24 h. The solid powder was collected, which was a two-dimensional Ti3C2-based cobalt single-atom catalytic material rich in titanium vacancies, labeled as Co / SA-Ti3C2.
[0012] Preferably, the MAX in step (1) is Ti3AlC2 powder, and the water bath temperature is 35°C.
[0013] Preferably, the centrifugal speed in step (2) is controlled at 3500 rpm, and each centrifugal treatment is 10 minutes, and distilled water is used for washing, and the number of washing times is 7 times.
[0014] Preferably, in step (3), distilled water is used to transfer the solid, and the shaking needs to be mechanical for 1 hour combined with manual shaking for 1 hour, and the low-temperature storage condition is set to 4°C.
[0015] Preferably, in step (4), the concentration of the NaBH4 aqueous solution is 10 mg / mL, the centrifugal speed is controlled at 8000 rpm, the centrifugal treatment time is 10 min, the freeze-drying time is 24 h, and the ultrasonic condition is an ice bath atmosphere created by circulating chilled water.
[0016] Preferably, the concentration of the solid aqueous solution in step (5) is 1 mg / mL, and the concentration of the Co(NO3)2·6H2O aqueous solution is 1 mg / mL.
[0017] Preferably, the stirring speed in step (5) is 650 rpm, and the ultrasonic condition is an ice bath atmosphere created by circulating chilled water.
[0018] Preferably, the centrifugal speed in step (5) is controlled at 10000 rpm, and each centrifugal treatment is 10 min, and distilled water is used for washing, and the number of washing times is 2 times.
[0019] A two-dimensional Ti3C2-based cobalt single-atom catalytic material rich in titanium vacancies was prepared by the above method, in which cobalt was dispersed on the Ti3C2 substrate at the atomic level, presenting an obvious two-dimensional layered structure, and the loading amount of cobalt single atoms was 1.64wt%.
[0020] The above-mentioned method for activating PMS and degrading OMPs by a two-dimensional Ti3C2-based cobalt single-atom catalytic material rich in titanium vacancies. The preparation method developed by the present invention not only makes up for the problems of atomic agglomeration, 1 The technical defect of poor O2 selective generation solves the problem of incompatibility between catalytic activity and structural stability. PMS is activated to degrade various OMPs in water at a lower operating cost. The reaction steps are as follows:
[0021] Under normal temperature and pressure conditions, Co / SA-Ti3C2 and PMS are added to an aqueous solution containing OMPs, and the reaction is allowed to occur under magnetic stirring.
[0022] Preferably, the reaction is carried out in a glass conical flask, the magnetic stirring rate used is 650 rpm, and the reaction time is 20 min.
[0023] Preferably, the concentration of the OMPs is 3 mg / L.
[0024] Preferably, the addition concentration of Co / SA-Ti3C2 is 25 mg / L.
[0025] Preferably, the addition concentration of the PMS is 50 mg / L.
[0026] Preferably, the OMPs include ranitidine (RAN), rhodamine B (RhB), methyl orange (MO), methylene blue (MB), norfloxacin (NFX), ciprofloxacin (CIP), tetracycline hydrochloride (TC), bisphenol A (BPA) and carbamazepine (CBZ).
[0027] The present invention adopts the coupling method of etching-stripping-reduction to prepare a two-dimensional Ti3C2-based cobalt single-atom peroxymonosulfate (PMS) activator, which creates abundant titanium vacancies without destroying the original layered structure of Ti3C2, and makes the single-atom cobalt evenly distributed and highly exposed to obtain excellent catalytic activity. By introducing abundant titanium vacancies, the charge transfer efficiency of the Ti3C2 layered surface is improved, so that it can maintain long-term catalytic activity. Its unique two-dimensional layered structure can effectively bind the toxic Co leached from the material. 2+ , to reduce the risk of secondary water pollution. In addition, Ti3C2-based cobalt single-atom two-dimensional materials can induce 1 O2 is generated and multiple oxidation mechanisms are stimulated to quickly degrade difficult-to-degrade organic micropollutants in water media. It can also resist the interference of high concentrations and multiple types of inorganic anions. It shows great application potential in the field of water pollution control with the advantages of green environmental protection and low cost.
[0028] Compared with the conventional technology, the advantages and effects of the present invention are as follows:
[0029] (1) The method for preparing Co / SA-Ti3C2 of the present invention does not require a high temperature process, reduces energy consumption, and avoids the problem of high material synthesis cost and being unfavorable to environmental safety.
[0030] (2) The method for preparing Co / SA-Ti3C2 of the present invention retains the original layered structure of Ti3C2, avoids the problem of single-atom cobalt agglomeration, and forms highly dispersed catalytic active centers.
[0031] (3) The Co / SA-Ti3C2 activated material prepared by the present invention has high structural stability, can resist high concentrations of inorganic anions, and effectively binds the toxic Co leached from the material. 2+ , to avoid secondary pollution to the water environment.
[0032] (4) The Co / SA-Ti3C2 activated material prepared by the present invention can induce 1 O2 is generated and multiple oxidation mechanisms are stimulated to rapidly degrade difficult-to-degrade organic micropollutants in water media.
[0033] (5) The Co / SA-Ti3C2 activated material prepared by the present invention has low synthesis cost, simple required equipment, and is suitable for large-scale industrial production.
[0034] (6) The Co / SA-Ti3C2 activated material prepared by the present invention does not require additional energy input (light, electricity, heat, etc.) during the PMS activation process, which reduces the operating cost. In addition, the process flow is simple, the operability is strong, the activation time is short, the performance is stable, and the material input is small, so it has broad practical application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is the X-ray crystal diffraction pattern (XRD) of the two-dimensional Ti3C2-based cobalt single-atom catalytic material Co / SA-Ti3C2 rich in titanium vacancies prepared in Example 1.
[0036] Figure 2 In the figure, (a) and (b) are scanning electron microscope images (SEM) of the two-dimensional Ti3C2-based cobalt single-atom catalytic material (Co / SA-Ti3C2) rich in titanium vacancies prepared in Example 1 at different magnifications; (c) and (d) are scanning transmission electron microscope images (STEM); (e), (f), (g) and (h) are X-ray energy dispersion diagrams (EDS) of oxygen, cobalt, carbon and titanium elements, respectively.
[0037] Figure 3 This is the EPR spectrum of the active oxidative species detected in the reaction system using DMPO as a capture agent in Example 2.
[0038] Figure 4This is a comparison of the kinetics of RAN removal by the present invention and different advanced oxidation technologies on the market in Example 5. DETAILED DESCRIPTION
[0039] In order to make the purpose, technology and advantages of the present invention more clear, the following is a detailed description with reference to the accompanying drawings and specific embodiments. The embodiments are only for illustrating the present invention and are not intended to limit the present invention.
[0040] The raw materials used in the present invention are all conventional commercially available products.
[0041] Example 1
[0042] This example compares the effect of Co / SA-Ti3C2 activated PMS on oxidative degradation of different OMPs in an aqueous environment, including ranitidine (RAN), rhodamine B (RhB), methyl orange (MO), methylene blue (MB), norfloxacin (NFX), ciprofloxacin (CIP), tetracycline hydrochloride (TC), bisphenol A (BPA), and carbamazepine (CBZ).
[0043] (1) Preparation of Co / SA-Ti3C2 catalytic material in the present invention: 4 g LiF was added to a polytetrafluoroethylene beaker containing 60 mL HCl (9 mol / L) solution, and the mixture was mechanically stirred at a speed of 650 rpm. After the mixture was completely dissolved, 2 g Ti3AlC2 powder was slowly added, and the mixture was stirred in a water bath at 35°C for 24 h for thorough etching. After removing the floating white layer from the etched solution, the solution was centrifuged and washed seven times with distilled water at 3500 rpm for 10 min until the pH of the supernatant was close to neutral. The solid precipitate was transferred to a screw-capped reagent bottle with distilled water. The solution was shaken mechanically for 1 h and manually for 1 h until a dark green viscous substance could be suspended on the inner wall of the reagent bottle. The solution was then configured into 500 mL of a 1 mg / mL aqueous solution, and 10 mL of a 10 mg / mL NaBH4 aqueous solution was added. The solution was mixed and stirred at 650 rpm for 30 min, and then treated with ice bath ultrasound (ice bath atmosphere created by circulating chilled water) for 1 h. The treated solution was centrifuged at 8000 rpm for 10 min, freeze-dried for 24 h, and the solid powder was collected. The above solid powder was prepared into 500 mL of aqueous solution (1 mg / mL), ultrasonically dissolved for 30 minutes, 22.88 mL (1 mg / mL) of Co(NO3)2·6H2O solution was slowly added to the solution, magnetically stirred at 650 rpm for 30 minutes, ultrasonicated on an ice bath for 1 hour, the centrifugal speed was controlled at 10000 rpm, the centrifugal treatment time was 10 minutes, washed twice by centrifugation with distilled water, and freeze-dried for 24 hours. The collected solid powder was a two-dimensional Ti3C2-based cobalt single-atom catalytic material rich in titanium vacancies, labeled as Co / SA-Ti3C2.
[0044] The XRD and SEM / STEM-EDS images of the prepared Co / SA-Ti3C2 are shown in Figure 1 and 2 As shown. Through the SEM / STEM-EDS image, it can be observed that Co / SA-Ti3C2 presents a clear lamellar structure and the elements are evenly distributed on its surface. Figure 2 It can be clearly seen in (c) that the material contains a large number of Ti vacancies, and Co is anchored on the Ti3C2 substrate in the form of single atoms.
[0045] (2) Prepare a 3 mg / L RAN aqueous solution for later use.
[0046] (3) Add 200 mL of the RAN aqueous solution prepared in (2) and adjust the pH value of the aqueous solution to neutral (pH = 7.0). Add 2.5 mg of Co / SA-Ti3C2, disperse evenly under ultrasonication, and place in a water bath at 25°C. The adsorption time is 10 min until the catalytic material reaches the adsorption saturation state, then add 5.0 mg of PMS, control the speed to 650 rpm under magnetic stirring conditions, take samples at regular intervals, and test and analyze using a UV-visible spectrophotometer.
[0047] (4) The pollutant added to the reaction vessel was changed from 3 mg / L RAN to 3 mg / L MO, and the other conditions remained the same as (3).
[0048] (5) The pollutant added to the reaction vessel was changed from 3 mg / L RAN to 3 mg / L MB, and the other conditions remained the same as (3).
[0049] (6) The pollutant added to the reaction vessel was changed from 3 mg / L RAN to 3 mg / L NFX, and the other conditions remained the same as (3).
[0050] (7) The pollutant added to the reaction vessel was changed from 3 mg / L RAN to 3 mg / L CIP, and the other conditions remained the same as (3).
[0051] (8) The pollutant added to the reaction vessel was changed from 3 mg / L RAN to 3 mg / L TC, and the other conditions remained the same as (3).
[0052] (9) The pollutant added to the reaction vessel was changed from 3 mg / L RAN to 3 mg / L BPA, and the other conditions remained the same as (3).
[0053] The removal effects of different OMPs under Co / SA-Ti3C2 and PMS systems are shown in Table 1.
[0054] Table 1 Removal rates of different OMPs
[0055] Organic micropollutants RAN MO MB NFX CIP TC BPA 16 minutes removal rate % 100% 95.1% 96.8% 81.0% 87.1% 90.4% 86.5% 30 minutes removal rate % 100% 100% 100% 100% 100% 100% 100%
[0056] As shown in Table 1, during the 16-minute rapid catalytic oxidation reaction, the removal rate of Co / SA-Ti3C2 catalytically activated PMS oxidation degradation of different organic micropollutants was above 80%. When the reaction time was extended to 30 minutes, the removal rate of the above OMPs reached 100%. The high efficiency of the prepared Co / SA-Ti3C2 in removing organic micropollutants is closely related to its highly exposed cobalt single atom active sites, indicating that the heterogeneous oxidation process generally has non-selective oxidation degradation ability for organic micropollutants in water.
[0057] Example 2
[0058] Example 1 proves that the Co / SA-Ti3C2 prepared by the present invention has excellent catalytic activity and has great practical application potential. In this example, RAN is used as the target pollutant, several common types of actual water bodies are selected, and the catalytic activity of Co / SA-Ti3C2 in different water media is compared.
[0059] (1) The preparation method of Co / SA-Ti3C2 catalytic material is the same as step (1) in Example 1.
[0060] (2) Use different water bodies as the medium to prepare a RAN aqueous solution with a concentration of 3 mg / L for later use.
[0061] (3) Select a 250mL stoppered conical flask as the reaction container, add 200mL of the RAN aqueous solution prepared in (2), and adjust the pH value of the aqueous solution to neutral (pH = 7.0). Add 2.5mg of Co / SA-Ti3C2, disperse it evenly by ultrasonication, and place it in a water bath to control the temperature at 25°C. The adsorption time is 10min, until the catalytic material reaches the adsorption saturation state, then add 5.0mg of PMS, control the speed to 650rpm under magnetic stirring conditions, take samples at regular intervals, and test and analyze using a UV-visible spectrophotometer.
[0062] (4) Add 50 μL of capture agent aqueous solution (DMPO / TEMP), mix well, and then absorb with a capillary tube. Then put it in a quartz tube and place it in the EPR (Bruker EMXplus-6 / 1, Germany) sample chamber to measure active oxidative species. Figure 3 shown.
[0063] The degradation effects of RAN in different water environments are shown in Table 2.
[0064] Table 2 Removal effect of RAN in different water media
[0065] Different water media Ultrapure water Tap water River Water Lake Secondary sedimentation tank effluent 20 minutes removal rate % 100% 100% 100% 67.5% 69.1% 30 minutes removal rate % 100% 100% 100% 100% 84.0% 60 minutes removal rate % 100% 100% 100% 100% 100%
[0066] As shown in Table 2, the Co / SA-Ti3C2 prepared by the present invention can remove RAN by 100% within 20 minutes when ultrapure water, tap water and river water are used as the medium. By extending the reaction time, RAN can also be completely removed when lake water and secondary sedimentation tank effluent are used as the medium. This proves that the catalytic material prepared by the present invention is highly practical and can adapt to different environmental water media to achieve catalytic activation of PMS to effectively remove target pollutants. In addition, Figure 3 It can be seen that during the oxidative degradation of RAN, DMPO-SO4 ·- , DMPO-·OH and TEMP- 1 The signals of O2 can be captured, indicating that Ti3C2-based cobalt single-atom two-dimensional materials can induce 1 O2 is generated and multiple oxidation mechanisms are stimulated to quickly degrade difficult-to-degrade organic micropollutants in water media. It shows great application potential in the field of water pollution control with its advantages of green environmental protection and high efficiency.
[0067] Example 3
[0068] Examples 1 and 2 demonstrate that the Co / SA-Ti3C2 prepared by the present invention has excellent catalytic activity characteristics, but structural stability is also another key feature of the material. In this example, the leaching risk of metal cobalt ions in Co / SA-Ti3C2 prepared under different pH conditions (pH=3.0, pH=5.0, pH=7.0, pH=9.0, pH=11.0) was evaluated by ICP-OES / MS technology.
[0069] (1) The preparation method of Co / SA-Ti3C2 catalytic material is the same as step (1) in Example 1.
[0070] (2) Prepare a 3 mg / L RAN aqueous solution for later use.
[0071] (3) Select a 250 mL conical flask with a stopper as the reaction container, add 200 mL of the RAN aqueous solution prepared in (2), and adjust the initial pH value of the aqueous solution to the set value (pH = 3.0, pH = 5.0, pH = 7.0, pH = 9.0, pH = 11.0). Add 2.5 mg of Co / SA-Ti3C2, disperse it evenly by ultrasonication, and place it in a water bath to control the temperature at 25°C. The adsorption time is 10 min, until the catalytic material reaches the adsorption saturation state, and then add 5.0 mg of PMS. Under magnetic stirring conditions, control the speed to 650 rpm, take samples at regular intervals, and use ICP-OES / MS (Agilent 5110, USA) for testing and analysis.
[0072] The leaching concentration of cobalt ions was tested under different initial pH conditions. The results are shown in Table 3.
[0073] Table 3 Leaching concentration of cobalt ions at different initial pH values
[0074] Initial pH of solution pH=3.0 pH=5.0 pH=7.0 pH=9.0 pH=11.0 Cobalt ion leaching concentration (mg / L) 0.06 0.05 0.03 0.02 0.01
[0075] As shown in Table 3, under different solution initial pH conditions, after the catalytic oxidation reaction of Co / SA-Ti3C2, the leaching concentration of cobalt ions is much lower than the surface water limit, indicating that the unique two-dimensional layered structure and the unique coordination environment of the cobalt element of the Co / SA-Ti3C2 prepared by the present invention enhance its structural stability and can effectively bind the toxic Co leached from the material. 2+ , in order to reduce the risk of secondary water pollution.
[0076] Example 4
[0077] This example determines the different types and concentrations of inorganic anions (Cl — ,SO4 2— ,H2PO4 — ,NO3 — and HPO4 2— ) under the condition of the presence of Co / SA-Ti3C2, the effect of PMS activation on oxidative degradation of RAN.
[0078] (1) The preparation method of Co / SA-Ti3C2 catalytic material is the same as step (1) in Example 1.
[0079] (2) Prepare a 3 mg / L RAN aqueous solution for later use.
[0080] (3) Select a 250mL stoppered conical flask as the reaction container, add 200mL of the RAN aqueous solution prepared in (2), and adjust the pH value of the aqueous solution to neutral (pH = 7.0). Add 2.5mg of Co / SA-Ti3C2, disperse it evenly by ultrasonication, and place it in a water bath at 25°C. The adsorption time is 10min, until the catalytic material reaches the adsorption saturation state, then add 5.0mg of PMS, add different concentrations (1mM, 5mM, 10mM and 200mM) of NaCl, control the speed to 650rpm under magnetic stirring conditions, take samples at regular intervals, and test and analyze using a UV-visible spectrophotometer.
[0081] (4) Na2SO4 of different concentrations (1 mM, 5 mM, 10 mM and 200 mM) was added to replace NaCl, and other conditions remained the same as (3).
[0082] (5) NaH2PO4 of different concentrations (1 mM, 5 mM, 10 mM and 200 mM) was added to replace NaCl, and other conditions remained the same as (3).
[0083] (6) Different concentrations (1 mM, 5 mM, 10 mM and 200 mM) of NaNO3 were added to replace NaCl, and other conditions remained the same as (3).
[0084] (7) Na2HPO4 of different concentrations (1 mM, 5 mM, 10 mM and 200 mM) was added to replace NaCl, and other conditions remained the same as (3).
[0085] The degradation effect of RAN in the presence of different types of inorganic anions is shown in Table 4.
[0086] Table 4 Effects of different concentrations and types of inorganic anions on RAN removal efficiency
[0087] Different inorganic anion concentrations <![CDATA[Cl - ]]> <![CDATA[SO4 2- ]]> <![CDATA[H2PO4 - ]]> <![CDATA[NO3 - ]]> <![CDATA[HPO4 2- ]]> RAN removal rate at 1mM 59.3% 78.3% 81.0% 78.2% 97.8% RAN removal rate at 5mM 76.4% 92.9% 97.8% 65.3% 96.3% RAN removal rate at 10mM 84.5% 98.7% 98.3% 47.8% 94.5% RAN removal rate at 200mM 97.0% 97.4% 94.2% 87.1% 93.0%
[0088] As shown in Table 4, during the 20-min rapid catalytic oxidation reaction, after adding different types of inorganic anions to the Co / SA-Ti3C2 and PMS system, the target pollutant RAN still has a high removal rate. In the presence of high concentrations of inorganic anions, the removal rate of RAN remains above 85%, proving that the catalytic material prepared by the present invention has good stability and can resist the interference of high concentrations and multiple types of inorganic anions.
[0089] Example 5
[0090] This example compares the effectiveness of Co / SA-Ti3C2 prepared in Example 1 with different types of advanced oxidation techniques in activating PMS to oxidatively degrade RAN.
[0091] (1) The preparation method of Co / SA-Ti3C2 catalytic material is the same as step (1) in Example 1.
[0092] (2) Prepare a 3 mg / L RAN aqueous solution for later use.
[0093] (3) Select a 250mL stoppered conical flask as the reaction container, add 200mL of the RAN aqueous solution prepared in (2), and adjust the pH value of the aqueous solution to neutral (pH = 7.0). Add 2.5mg of Co / SA-Ti3C2, disperse it evenly by ultrasonication, and place it in a water bath to control the temperature at 25°C. The adsorption time is 10min, until the catalytic material reaches the adsorption saturation state, then add 5.0mg of PMS, control the speed to 650rpm under magnetic stirring conditions, take samples at regular intervals, and test and analyze using a UV-visible spectrophotometer.
[0094] (4) Using the most scientific reaction kinetics formula (1), the reaction rates (k) of different advanced oxidation technologies were calculated and compared to evaluate the RAN oxidation degradation efficiency.
[0095] k=1 / m×dC RAN / d t (1)
[0096] Where k is the reaction rate, m is the catalyst dosage, C RAN is the RAN concentration, and t is the reaction time.
[0097] The comparison of RAN removal efficiency evaluation when different advanced oxidation technologies are used is shown in Table 5 and Figure 4 shown.
[0098] Table 5 Comparison of RAN removal efficiency evaluation when using different advanced oxidation technologies
[0099]
[0100] From Table 5 and Figure 4 It can be seen that the reaction rate constant calculated by formula (1) can intuitively reflect the treatment efficiency of this technology. Compared with different advanced oxidation technologies on the market, the efficiency of Co / SA-Ti3C2 catalytic activation of PMS oxidation degradation of RAN has obvious advantages, which is specifically reflected in the small amount of material added and the significant reduction in operating costs, which can meet the current scientific and technological needs of RAN pollution control. The reaction rate constant of the Co / SA-Ti3C2 catalytic activation of PMS oxidation degradation of RAN prepared by the present invention is 2.92 to 3550.31 times that of the advanced oxidation technology currently used in the market, which fully demonstrates that the Co / SA-Ti3C2 of the present invention has more excellent performance and practical potential.
[0101] Example 6
[0102] This example evaluates the cyclic use of Co / SA-Ti3C2 catalytically activated PMS for oxidative degradation of RAN.
[0103] (1) The preparation method of Co / SA-Ti3C2 catalytic material is the same as step (1) in Example 1.
[0104] (2) Prepare a 3 mg / L RAN aqueous solution for later use.
[0105] (3) Select a 250mL stoppered conical flask as the reaction container, add 200mL of the RAN aqueous solution prepared in (2), and adjust the pH value of the aqueous solution to neutral (pH = 7.0). Add 2.5mg of Co / SA-Ti3C2, disperse it evenly by ultrasonication, and place it in a water bath to control the temperature at 25°C. The adsorption time is 10min, until the catalytic material reaches the adsorption saturation state, then add 5.0mg of PMS, control the speed to 650rpm under magnetic stirring conditions, take samples at regular intervals, and test and analyze using a UV-visible spectrophotometer.
[0106] (4) The Co / SA-Ti3C2 in (3) was filtered out through a water filter membrane with a pore size of 0.22 μm and a second catalytic experiment was carried out. Other conditions remained the same as in (3).
[0107] (5) The Co / SA-Ti3C2 in (4) was filtered out through a water filter membrane with a pore size of 0.22 μm and a third catalytic experiment was carried out. The other conditions remained the same as (3).
[0108] (6) The Co / SA-Ti3C2 in (5) was filtered out through a water filter membrane with a pore size of 0.22 μm and the fourth catalytic experiment was carried out. The other conditions remained the same as (3).
[0109] (7) The Co / SA-Ti3C2 in (6) was filtered out through a water filter membrane with a pore size of 0.22 μm and the fifth catalytic experiment was carried out. The other conditions remained the same as (3).
[0110] (8) The Co / SA-Ti3C2 in (7) was filtered out through a water filter membrane with a pore size of 0.22 μm and the sixth catalytic experiment was carried out. The other conditions remained the same as (3).
[0111] (9) The Co / SA-Ti3C2 in (8) was filtered out through a water filter membrane with a pore size of 0.22 μm and the seventh catalytic experiment was carried out. The other conditions remained the same as (3).
[0112] (10) The Co / SA-Ti3C2 in (9) was filtered out through a water filter membrane with a pore size of 0.22 μm and the eighth catalytic experiment was carried out. The other conditions remained the same as (3).
[0113] (11) The Co / SA-Ti3C2 in (10) was filtered out through a water filter membrane with a pore size of 0.22 μm and the ninth catalytic experiment was carried out. The other conditions remained the same as (3).
[0114] (12) The Co / SA-Ti3C2 in (11) was filtered out through a water filter membrane with a pore size of 0.22 μm and the tenth catalytic experiment was carried out. The other conditions remained the same as (3).
[0115] The recycling status of the catalytic material Co / SA-Ti3C2 prepared by the present invention after 10 activations of PMS to oxidatively degrade the target pollutant RAN is shown in Table 6.
[0116] Table 6 Recycling of RAN degraded by Co / SA-Ti3C2
[0117]
[0118]
[0119] As shown in Table 6, after 10 cycles of using Co / SA-Ti3C2 to catalyze the activation of PMS to oxidatively degrade RAN, the corresponding RAN removal rate shows an acceptable downward trend as the number of times increases, but it can still be maintained above 75%, which has surpassed most of the single-atom catalytic materials on the market. The above examples fully demonstrate that the Co / SA-Ti3C2 prepared by the present invention has excellent catalytic stability, can be reused continuously for multiple times, and shows significant commercial value.
[0120] In summary, the two-dimensional Ti3C2-based cobalt single-atom catalytic material (Co / SA-Ti3C2) rich in titanium vacancy structural defects synthesized in the present invention can activate PMS to produce 1 The active substance, which is mainly composed of O2, can achieve a degradation efficiency of more than 80% for OMPs in water in a short time at room temperature, and has strong resistance to a variety of inorganic anions. In addition, the leaching amount of cobalt ions in the catalytic material is extremely low, and it has excellent structural stability. It can be recycled continuously for many times without causing secondary pollution to the water environment, showing the broad application prospects of Co / SA-Ti3C2 in the field of water pollution control.
Claims
1. A method for preparing a Ti3C2-based cobalt single-atom two-dimensional material rich in titanium vacancies, characterized in that: The steps include: (1) Add LiF and hydrochloric acid solution into a polytetrafluoroethylene beaker and stir evenly. After they are completely dissolved, add Ti3AlC2 powder and stir in a water bath for thorough etching. (2) centrifuging and washing the etched solution until the pH of the supernatant is neutral, and collecting the solid precipitate; (3) Transfer the solid precipitate into a reagent bottle and continue shaking until a dark green viscous substance can be seen hanging on the inner wall of the reagent bottle; (4) dispersing the dark green viscous substance into water, adding NaBH4 aqueous solution, stirring, and then performing ice bath ultrasonic treatment, and then centrifuging and freeze-drying the treated solution to collect solid powder; (5) The solid powder is dispersed in water, and a Co(NO3)2·6H2O aqueous solution is added, stirred, and then subjected to an ice bath ultrasonic treatment. The treated solution is then centrifuged and freeze-dried, and the solid powder is collected to obtain a Ti3C2-based cobalt single-atom two-dimensional material rich in titanium vacancies.
2. The method for preparing the Ti3C2-based cobalt single-atom two-dimensional material rich in titanium vacancies according to claim 1, characterized in that: The stirring in a water bath in step (1) specifically includes stirring in a water bath at a temperature of 35° C. for 24 hours.
3. The method for preparing the Ti3C2-based cobalt single-atom two-dimensional material rich in titanium vacancies according to claim 1, characterized in that: In step (2), the centrifugal speed is controlled at 3500 rpm, and each centrifugal treatment is 10 minutes. Distilled water is used for washing, and the number of washing times is 7 times.
4. The method for preparing the Ti3C2-based cobalt single-atom two-dimensional material rich in titanium vacancies according to claim 1, characterized in that: In step (3), the shaking is performed by mechanical shaking for 1 hour combined with manual shaking for 1 hour.
5. The method for preparing the Ti3C2-based cobalt single-atom two-dimensional material rich in titanium vacancies according to claim 1, characterized in that: In step (4), the concentration of the NaBH4 aqueous solution is 10 mg / mL, the stirring speed is 650 rpm, the centrifugal speed is controlled at 8000 rpm, the centrifugal treatment time is 10 min, and the freeze-drying time is 24 h.
6. The method for preparing the Ti3C2-based cobalt single-atom two-dimensional material rich in titanium vacancies according to claim 1, characterized in that: In step (5), the concentration of the Co(NO3)2·6H2O aqueous solution is 1 mg / mL, the stirring speed is 650 rpm, the centrifugal speed is controlled at 10000 rpm, and each centrifugal treatment is 10 min. Distilled water is used for washing, and the washing number is 2 times.
7. A Ti3C2-based cobalt single-atom two-dimensional material rich in titanium vacancies prepared by the method of any one of claims 1 to 6.
8. The titanium vacancy-rich Ti3C2-based cobalt single-atom two-dimensional material according to claim 7, characterized in that: Cobalt is dispersed on the Ti3C2 substrate at the atomic level, presenting a two-dimensional layered structure, and the loading amount of cobalt single atoms is 1.64wt%.
9. Use of the Ti3C2-based cobalt single-atom two-dimensional material rich in titanium vacancies as described in claim 7 or 8 as a catalyst to activate PMS to oxidatively degrade OMPs.
10. The use according to claim 9, characterized in that: The OMPs include ranitidine, rhodamine B, methyl orange, methylene blue, norfloxacin, ciprofloxacin, tetracycline hydrochloride, bisphenol A and carbamazepine.
Citation Information
Patent Citations
Preparation method of surface organic modified titanium carbide nanosheet
CN108557822A
Method for degrading organic pollutants in water by using nitrogen-doped porous carbon anchored monatomic cobalt catalyst to activate persulfate
CN112408577A
Preparation method for loading monatomic iron-based metal on surface of titanium carbide and application of monatomic iron-based metal
CN114471646A
Preparation and application of CoS / Ti3C2 MXene composite material
CN114849748A
Cu / MXene monatomic catalyst as well as preparation method and application thereof
CN115090286A
